2016
DOI: 10.4103/2347-5625.177394
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress and coping in recently discharged postsurgical cancer patients

Abstract: Objective:Cancer patients and survivors need to cope with various stressful situations and problems even after treatment. In this study, we sought to investigate psychological stress and coping in recently discharged postsurgical cancer patients.Methods:A mail-in questionnaire survey about stress response, perceived illness-related demands, and coping strategies and styles was administered to postsurgical Japanese cancer patients. The questionnaires were returned a week after the patients’ discharge from the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The reason for this may be that patients face great psychological pressure after being diagnosed with cancer and will show a negative emotion of letting go. Although acceptance-resignation can reduce the psychological pressure of patients in the short term [ 42 ], it will put patients in a negative mood in the long run, affect their initiative, and hinder the implementation of their health behavior, and is not conducive to patients’ perception of BF. It is thus suggested that medical staff strengthen the psychological guidance of patients and guide them in using positive coping styles to alleviate psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be that patients face great psychological pressure after being diagnosed with cancer and will show a negative emotion of letting go. Although acceptance-resignation can reduce the psychological pressure of patients in the short term [ 42 ], it will put patients in a negative mood in the long run, affect their initiative, and hinder the implementation of their health behavior, and is not conducive to patients’ perception of BF. It is thus suggested that medical staff strengthen the psychological guidance of patients and guide them in using positive coping styles to alleviate psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…This scale is capable of measuring temporary psychological changes induced by stressful situations. The SRS-18 is sufficiently valid and reliable and has been standardized for the Japanese population [ 68 , 69 ]. The scale consists of 18 items and the responses are recorded on a 4-point scale (0 = not at all to 3 = exactly so).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies included in this review were performed by nurses and based their interventions on the theorical contribution by Transactional Model of Stress and Coping (9) . Although this model is derived from the principles of health psychology, and considering that autonomous nursing interventions should be based on nursing theories and expertise, this model is frequently used by oncological nurses due to its positive effect on cancer patients' psychological health, especially when the intervention focus is illness adaptation, stress management and coping mechanisms (75)(76)(77)(78)(79)(80)(81) . Nurses concerns with disease adaptation are not confined to the Psychology's body of evidence, as evidenced by use of the Adaptation Model of Nursing (82)(83) as theoretical framework for one of the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%